2019
DOI: 10.1093/jmammal/gyz153
|View full text |Cite
|
Sign up to set email alerts
|

A continent-scale study of the social structure and phylogeography of the bent-wing bat, Miniopterus schreibersii (Mammalia: Chiroptera), using new microsatellite data

Abstract: Miniopterus schreibersii is a cave-dwelling bat species with a wide distribution in the western Palearctic spanning southern and central Europe, North Africa, Anatolia, the Middle East, and the Caucasus. We investigated the social structure and its effects on the genetic makeup of this species, using 10 nuclear microsatellite markers and a partial fragment of the mitochondrial cytochrome b gene. Samples were examined from the species' entire circum-Mediterranean range. Local structuring that was previously det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 101 publications
3
12
0
Order By: Relevance
“…The shallow genetic differentiation in M. schreibersii previously found [ 95 ] and posteriorly confirmed [ 59 , 96 ] by other authors suggests a recent and rapid postglacial re-colonization of Europe, probably from Anatolia acting as a single glacial refugium, which showed the highest allelic richness [ 59 , 96 ]. Unlike the pattern of H .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The shallow genetic differentiation in M. schreibersii previously found [ 95 ] and posteriorly confirmed [ 59 , 96 ] by other authors suggests a recent and rapid postglacial re-colonization of Europe, probably from Anatolia acting as a single glacial refugium, which showed the highest allelic richness [ 59 , 96 ]. Unlike the pattern of H .…”
Section: Discussionsupporting
confidence: 78%
“…Some author suggested that M. s. schreibersii (Kuhl 1817) is a typical representative to Europe, North Africa, and Asia Minor and M. s. pallidus Thomas 1907 is present in the Asian part of Turkey [ 58 ]. Recently, the population structure of M. schreibersii was analyzed using microsatellite and mtDNA [ 59 ]. It was found an approximately uniform distribution of nuclear DNA (nDNA) alleles in contrast with mtDNA, which showed more geographic structuring [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, such patterns are attributable to adaptive introgression of mtDNA, demographic disparities, and sex-biased asymmetries; in some cases they found evidence for hybrid zone movement or human agency. Discordant patterns of variation between mitochondrial and nuclear DNA have been reported in at least six other families of bats (Nesi et al 2011;Furman et al 2014;Naidoo et al 2016;Hassanin et al 2018;Demos et al 2019a;Gürün et al 2019). Gürün et al (2019) implicated the role of sex-biased dispersal in causing such discordance, male dispersal spreading nuclear variation farther and faster than the movement of mitochondria.…”
Section: Species Limitsmentioning
confidence: 73%